Measurement of the Components of the Tensor Analyzing Power in the Reaction γD → ppπ- at Low Proton Energies; Russian Physics Journal; Vol. 61, iss. 7 - Gauzshteyn (Gauzshtein) V. V. Vyacheslav Valerjevich; Zevakov S. A. Sergey Aleksandrovich; Levchuk M. I. Mikhail Ivanovich; Loginov A. Yu. Aleksey Yurievich; Lukonin S. E. Stanislav Evgenievich; Nikolenko D. M. Dmitry Mitrofanovich; Rachek I. A. Igor Anatoljevich; Sadykov R. Sh. Rustam Shagitovich; Toporkov D. K. Dmitry Konstantinovich; Shestakov Yu. V. Yury Vladimirovich (2018, 2018)
Title screen